XAB2 promotes Ku eviction from single-ended DNA double-strand breaks independently of the ATM kinase. Issue 17 (9th September 2021) - Sharma, Abhishek Bharadwaj; Erasimus, Hélène; Pinto, Lia; Caron, Marie-Christine; Gopaul, Diyavarshini; Peterlini, Thibaut; Neumann, Katrin; Nazarov, Petr V; Fritah, Sabrina; Klink, Barbara; Herold-Mende, Christel C; Niclou, Simone P; et al.
Abstract: Replication-associated single-ended DNA double-strand breaks (seDSBs) are repaired predominantly through RAD51-mediated homologous recombination (HR). Removal of the non-homologous end-joining (NHEJ) factor Ku from resected seDSB ends is crucial for HR. The coordinated actions of MRE11-CtIP nuclease activities orchestrated by ATM define one pathway for Ku eviction. Here, we identify the pre-mRNA splicing protein XAB2 as a factor required for resistance to seDSBs induced by the chemotherapeutic alkylator temozolomide. Moreover, we show that XAB2 prevents Ku retention and abortive HR at seDSBs induced by temozolomide and camptothecin, via a pathway that operates in parallel to the ATM-CtIP-MRE11 axis. Although XAB2 depletion preserved RAD51 focus formation, the resulting RAD51-ssDNA associations were unproductive, leading to increased NHEJ engagement in S/G2 and genetic instability. Overexpression of RAD51 or RAD52 rescued the XAB2 defects and XAB2 loss was synthetically lethal with RAD52 inhibition, providing potential perspectives in cancer therapy. Graphical Abstract: